Oromucosal lesions in women smokers: an Indian perspective - Shende, Vaishali Waghmare; Kaushik, Shruti; Nagpal, Indu (International Journal Of Community Medicine And Public Health, 2021)
Women smoking is looked down upon by Indian society. However, a young woman smoking is not a rare sight on college campuses in metro cities. Substantial body of literature indicates that nicotine is the major component which leads to addiction. The habit which starts to look cool and fashionable in no time becomes an addiction. Indian society, which doesn’t acknowledge that women are indulging in smoking, makes the whole fight about tobacco addiction a turbulent journey. As society doesn’t accept that women smoke, there is no need to create awareness about its gendered impact. The study was undertaken by evaluating the oromucosal conditions and haemoglobin levels of 100 women smokers. Smokers’ palate, smoking associated pigmentation on lips and calculus deposits were observed in most of the participants. The participants were not aware about the hormonal issues and detrimental side effects of smoking to their health.